2003
DOI: 10.1103/physrevb.67.165106
|View full text |Cite
|
Sign up to set email alerts
|

1/fnoise in electron glasses

Abstract: We show that 1/ f noise is produced in a 3D electron glass by charge fluctuations due to electrons hopping between isolated sites and a percolating network at low temperatures. The low frequency noise spectrum goes as ω −α with α slightly larger than 1. This result together with the temperature dependence of α and the noise amplitude are in good agreement with the recent experiments. These results hold true both with a flat, noninteracting density of states and with a density of states that includes Coulomb in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
3
23
0
1
Order By: Relevance
“…The effect of such a randomly changing field on localized electrons aside from from the hopping clusters should be qualitatively similar to that of thermal fluctuations that may lead to the 1/f noise, for example following one of the scenarios described in Refs. [22,23,24,25,26]. Recent experiments for hopping in quasi-3D samples [48,49], showing a very slow change of 1/f noise intensity at T → 0, seem qualitatively compatible with this interpretation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The effect of such a randomly changing field on localized electrons aside from from the hopping clusters should be qualitatively similar to that of thermal fluctuations that may lead to the 1/f noise, for example following one of the scenarios described in Refs. [22,23,24,25,26]. Recent experiments for hopping in quasi-3D samples [48,49], showing a very slow change of 1/f noise intensity at T → 0, seem qualitatively compatible with this interpretation.…”
Section: Discussionsupporting
confidence: 70%
“…In particular, many studies [18] have found that C (f ) /f ∝ 1/f p , where p is typically between 1 and 2. For the particular case of hopping conduction, two major theories of 1/f noise have been suggested, based, respectively, on "carrier number" fluctuations [22,23,24] and "mobility" fluctuations [25,26] as possible origins of the noise. Unfortunately, both theories have been developed for the case of substantially nonvanishing temperatures, for which an accurate numerical study of noise is difficult even with currently available advanced simulation algorithms and supercomputer resources.…”
Section: Current Fluctuationsmentioning
confidence: 99%
“…Another model involved unpaired and non-interacting electrons randomly hopping between traps with different spin orientations and a 1/f distribution of trap energies [14]. Quite often hopping conductivity models are used for 1/f noise in solid state systems [15][16][17] …”
Section: Clusters Of Interacting Two-level-systems (Tls)likely Due To Fmentioning
confidence: 99%
“…Existence of such correlated state will lead to NGC in the resistance noise in such systems [5]. We have investigated the development of such NGC in the fluctuation using two tests, namely, the direct method of the PDF and also the more sensitive second spectrum method.…”
mentioning
confidence: 99%